Da'wah Movement through Nahdlatul Ulama Coin as a Channel of Infaq and Sadaqah in Indonesia - Herman, Herman; Ridho, Ali; Malik, Rif'atul Khoiriah; Zubaidi, Advan Navis; Nisa, Faridhotun; Panaemalae, Razak (Jurnal Dakwah Risalah, 2024)
This research aims to find out how PCNU Bantul Regency utilizes the Da'wah Movement through NU Coin. This research is a descriptive qualitative research with a case study approach, the research location is PCNU Bantul Regency and focuses on four MWC NU. Data collection techniques are observation, interview, and documentation. The results of the research are: First, PCNU Bantul Regency conducts socialization activities to the community about the NU Coin program through religious activities (read: Pengajian, Tahlilan, Yasinan, Manaqiban, etc.), socialization activities also through brochures/pamphlets as well as online and offline mass media by involving various elements of society and government at the regional to village level. Second, the proceeds from NU Coin are used for the benefit of Islamic propagation ranging from community empowerment and, construction of public facilities and infrastructure including religious, social, health, and economy to education in Bantul Regency. The obstacle is the emergence of prejudice from some negative people towards the direction of the use of NU Coin, so they choose to make donations and alms independently.